Hugs and behaviour points: alternative education and the regulation of ‘excluded’ youth - Thomson, Pat; Pennacchia, Jodie (Taylor & Francis, 2015)
In England, alternative education (AE) is offered to young people formally excluded from school, close to formal exclusion or who have been informally pushed to the educational edges of their local school. Their behaviour is seen as needing to change. In this paper, we examine the behavioural regimes at work in 11 AE programmes. Contrary to previous studies and the extensive ‘best practice’ literature, we found a return to highly behaviourist routines, with talking therapeutic approaches largely operating within this Skinnerian frame. We also saw young people offered a curriculum largely devoid of languages, humanities and social sciences. What was crucial to AE providers, we argue, was that they could demonstrate ‘progress’ in both learning and behaviour to inspectors and systems. Mobilising insights from Foucault, we note the congruence between the external regimes of reward and punishment used in AE and the kinds of insecure work and carceral futures that might be on offer to this group of young people.